Magnetoabsorption spectra of intraexcitonic transitions in GaAs-(Ga,Al)As semiconductor quantum wells (2002)
ABSTRACT: We present a theoretical study, within the effective-mass approximation, of the magnetoabsorption spectra of intraexcitonic terahertz transitions of light-hole and heavy-hole confined magnetoexcitons in GaAs-~Ga,Al!As quantum wells. The semiconductor quantum wells are studied under magnetic fields applied in the growth direction of the semiconductor heterostructure. The various magnetoexciton states are obtained in the effective-mass approximation by an expansion of the exciton-envelope wave functions in terms of products of hole and electron quantum-well states with appropriate Gaussian functions for the various excitonic states. Intramagnetoexciton transitions are theoretically studied by exciting the allowed excitonic transitions with s1 ~or s2! far-infrared radiation circularly polarized in the plane of the GaAs-~Ga,Al!As quantum well. Theoretical results are obtained for the intramagnetoexciton transition energies and magneto-absorption spectra associated with excitations from 1s-like to 2p6 , and 3p6-like magnetoexciton states, and found in overall agreement with optically detected resonance measurements.